Back Cover: A Hydrogen‐Bonded Cyanide‐Bridged [Co2Fe2] Square Complex Exhibiting a Three‐Step Spin Transition (Angew. Chem. Int. Ed. 2/2017). Issue 2 (21st December 2016) - Nihei, Masayuki; Yanai, Yuta; Hsu, I.‐Jui; Sekine, Yoshihiro; Oshio, Hiroki
Abstract : Lord of the Dance Dynamic hydrogen‐bonding interactions and spin‐transition behavior play a key role in stabilizing intermediate phases in a multi‐step spin transition. In their Communication onpage 595 ff., M. Nihei, H. Oshio, et al. present a hydrogen‐bonding donor–acceptor system, comprising a spin transition‐active square complex [Co2 Fe2 ] and aromatic hydrogen‐bond‐donor molecules, which exhibits a three‐step spin transition in response to temperature.